The Evolution of Professional Training How Artificial Intelligence Technologies Can Accelerate the Learning. - Zaralli, Matteo (Routledge, Taylor & Francis Group, 2025)
This book is not just an analysis of the impact of emerging technologies on learning and professional development; it is also an invitation to reflect on the future of work, the nature of intelligence, and the evolution of human society in the digital age.